La escuela española de estilística y la pragmaestilística - López García, Ángel (Caplletra. Revista Internacional de Filologia, 2000)
The so-called «Spanish stylistic school», and specially pioneer linguists of this group as Amado Alonso and Dámaso Alonso, is presented in this article as a precedent of modern pragmastylistics in some interesting aspects. Nevertheless, as López García states, later authors –often considered members of this school– mainly devoted themselves of literary theory, far from the prior epistemological framework.